Kalkschwämme der Bremer Expedition nach Ost-Spitzbergen im Jahre 1889 (Prof. W. Kükenthal und Dr. A. Walter) - Breitfuss, L. L. (Leonid Lʹvovich) (VEB Gustav Fischer Verlag, 1896)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided.